Why do we choose the color red for danger? - Ellaisha Samari (2015)
This study is concerned with the evolutionary significance of red and the effects of our sensitivity to red on danger related issues. According to past research, red has been linked to several evolutionary psychology concepts such as foraging, romance, aggression and dominance. Particularly, primate color vision evolved from dichromatic to trichromatic color vision for finding food in the forest (Surridge, Osorio, & Mundy, 2003) and subsequently, this ability to detect red was also adapted for attracting mates by noticing the appearance of red colorations on body parts such as the face and genitalia (Dubuc, Allen, Maestripieri, & Higham, 2014). Of specific interest to this study is the implicit red-danger association that has been suggested in prior studies. Yet, no study has been done thus far to investigate if red would invoke feelings of danger should there be an implicit red-danger association. Furthermore, some have questioned the possibility of the association of red and danger of having evolutionary roots. If it were true that we have evolved mechanisms to associate red with danger, the mere act of perceiving a red stimulus in contexts where negative outcomes are salient would enhance the perception of danger. Thus, this study sought to explore the significance of the color red in relation to danger. To achieve the aim of this research paper, three studies were conducted in total. 60 participants were involved in a pilot study (Study 1) that determined participant’s baseline for what qualifies as significantly dangerous situations. Out of five displayed contexts, participants considered car racing, glacier hiking and boxing significantly dangerous. These situations were then adapted into the questionnaire for the actual study (Study 2). Subsequently, 40 participants were recruited and they each participated in Study 2 and 3. Study 2 investigated the effects of the color red (versus blue) on perceptions of danger using the software Inquisit Lab 4. Results showed no significant difference between both conditions (red and blue) as an influence on the perception of danger. Study 3 on the other hand sought to extend the findings of Study 2 by investigating the function of the color red in relation to displayed signs. Participants were asked to choose the best color that would attract attention of viewers both towards warning and non-warning related signs on Adobe Photoshop. Results showed that the color red was the most selected color for both signs, regardless of the context (dangerous or not dangerous). Thus, on the whole, these findings suggest that red does not significantly enhance perceptions of danger where negative outcomes are salient. Instead, red functions to alert viewers of impending danger, given its salient characteristic. Thus it is commonly used in areas where more serious warning is needed such as on traffic warning signs, to prevent the effect of these serious warnings from being diluted by other signs if there were all to be red too (Leonard, 1999).